Impact of home and clinical blood pressure variability on arteriosclerosis and metabolic indicators: a prospective multicenter registry study - Yu, Ha Young; Cha, Jung-Joon; Cho, Dong-Hyuk; Kim, Mi-Na; Oh, Se Won; Park, Jae Hyoung; Cho, Kyung-Hee; Shin, Seung Yong; Kim, Eung Ju; Joo, Hyung Joon (Clinical hypertension, 2025)
Blood pressure variability (BPV) represents an independent predictor of cardiovascular disease, distinct from mean blood pressure (BP). While home BP monitoring is widely recommended, the associations between home BPV and vascular, metabolic, and inflammatory markers remain unclear. We aimed to clarify these associations. We analyzed 519 hypertensive patients from a prospective multicenter registry. Home BPV was assessed using standard deviation, coefficient of variation (CV), average real variability, variability independent of the mean, and range. Patients were stratified by the median CV of home systolic BP (SBP). We used Pearson correlation coefficients to evaluate the relationships between home BPV and office BPV, metabolic parameters, and arterial stiffness indices. Based on stratification by the CV of home SBP, the high-BPV group was characterized by older age, a greater proportion of women, and a lower body mass index compared with the low-BPV group. Correlations between home and office BP were stronger for mean values than for variability indices. Home systolic BPV indices correlated positively with high-sensitivity C-reactive protein ( = 0.11-0.12, < 0.05) and with arterial stiffness parameters, particularly the second systolic peak ( = 0.23-0.35, ≤ 0.01), but not with lipid or glucose profiles. Home diastolic BPV indices exhibited weaker and inconsistent associations. Home systolic BPV showed consistent associations with vascular inflammation and arterial stiffness, but not with metabolic parameters. These findings support home BPV as a distinct cardiovascular risk marker with potential relevance for risk stratification and preventive management. ClinicalTrials.gov Identifier: NCT06394934.